PENGARUH TIME BUDGET PRESSURE DAN AUDIT FEE TERHADAP INDEPENDENSI DAN DAMPAKNYA TERHADAP KUALITAS AUDIT KAP SUMATERA BAGIAN TENGAH (PEKANBARU, BATAM DAN PADANG) - Nurul Ardiani; Amir Hasan; Hardi Hardi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2015)
This study was conducted to see the effect of time budget pressure and theindependence of the audit fee and the impact on audit quality. The object understudy is a Public Accounting Firm (KAP) Central Sumatera consisting ofPekanbaru, Batam and Padang.Testing is done with path analysis. Prior to the tests, conducted prior test dataquality (reliability and validity), test data normality and linearity test. Theseresults indicate that 1) Time budget pressure has no direct effect on audit quality,2) Audit fees have no direct influence on the quality of audit, 3) Independenceeffect on audit quality, 4) Time budget pressure effect on the independence, 5)Audit fees influential to independence, 6) Time budget pressure effect on auditquality, mediated by independence, 7) Audit fees affect the quality of the auditmediated by independence.